Indications and outcome of surgery for small nonfunctioning pancreatic neuroendocrine neoplasms (≤2 cm) - Bechtiger, Fabiola A.; Nießen, Anna; Hinz, Ulf; Lewosinska, Magdalena; Hamm, Alexander; Czigány, Zoltán; Billmann, Franck; Hackert, Thilo; Büchler, Markus W.; Schimmack, Simon (Surgery, 2025)
Objective - Optimal treatment strategies for small (≤2 cm) nonfunctioning pancreatic neuroendocrine neoplasms are still subject to discussion. The aim of this study was to analyze real-world data of patients with pancreatic neuroendocrine neoplasms ≤2 cm regarding the indications for surgery and long-term postresection survival. - Methods - All patients undergoing surgery for nonfunctioning pancreatic neuroendocrine neoplasms ≤2 cm between 2003 and 2023 were analyzed. Indications for surgery, clinicopathologic parameters, and long-term survival were assessed. Differences between pancreatic neuroendocrine neoplasms <1 cm and 1-2 cm were evaluated. - Results - Of a total of 806 resected pancreatic neuroendocrine neoplasms, 237 patients had a lesion ≤2 cm (29.4%), 85 of which were smaller than 1 cm. The 3 most common indications for surgery for pancreatic neuroendocrine neoplasms ≤2 cm were either suspicion of a non-neuroendocrine neoplasm malignancy (55.2%), suspicion of neuroendocrine tumor (25.9%), or obstruction of the pancreatic duct (9.4%). Tumor differentiation was 84% G1, 15% G2, and 1.3% G3. Noticeably, 5.1% of pancreatic neuroendocrine neoplasms ≤2 cm had lymph node metastasis (pN1). Five patients with a small pancreatic neuroendocrine neoplasm developed distant metastasis (pM1). The 10-year overall survival was 86.9% for <1 cm and 84.5% for 1-2 cm (P = .964). 10-year disease-free survival was 83.1% in patients with a pancreatic neuroendocrine neoplasms <1 cm and 81.1% for pancreatic neuroendocrine neoplasms 1-2 cm (P = .784). - Conclusion - Surgical treatment of small (≤2 cm) pancreatic neuroendocrine neoplasms provides excellent long-term survival. Since even small pancreatic neuroendocrine neoplasms can develop lymph node and distant metastases, treatment decisions should not be determined on the basis of tumor size alone.